Urgensi Pendidikan Pancasila Dalam Melawan Dampak Negatif Ideologi Transnasional - Sulistya Eviningrum; Salsabila Safirana Wibisono (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2024)
The Urgence of Pancasila Education in Against The Negative Impact of Transnational Ideology. Pancasila education is the part of National Education shich aims to improve the quality of human resources in Indonesia. The quality in question is a person who is full of responsibility which behaviour that reflects the implementation of Pancasila values in the life of nation and state. In practice, especiallu the next generation, it is increasingly expected and required to be able to anticipate changes related to the dynamics of culture, nation, state in international relations by thinking, acting, and behaving based on Pancasila. Reflecting on the advancement of technology today, the urgency of Pancasila education is increasingly visible with the rapid development of transnational ideology itself is widely discussed as a serious national threat. For this reason, the author conducted a study through a literature study of several references and legislation in order to find out more about the urgency of Pancasila education in countering the negative impacts of transnational ideology. Strengthening the values of Pancasila ideology through Pancasila education is a crucial thing that must be suceeded by all part of society.